2020
DOI: 10.3390/ijms21217836
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Autophagy in Breast Cancer

Abstract: Breast cancer is a heterogeneous disease consisting of different biological subtypes, with differences in terms of incidence, response to diverse treatments, risk of disease progression, and sites of metastases. In the last years, several molecular targets have emerged and new drugs, targeting PI3K/Akt/mTOR and cyclinD/CDK/pRb pathways and tumor microenvironment have been integrated into clinical practice. However, it is clear now that breast cancer is able to develop resistance to these drugs and the identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 185 publications
(213 reference statements)
0
46
0
Order By: Relevance
“…The PI3K/Akt/mTOR pathway plays an important role in the regulation of the cells’ cycle; it impacts the development and differentiation of cells [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ]. The PI3K/Akt/mTOR signaling pathway plays an important role in the processes of tumorigenesis.…”
Section: Introductionmentioning
confidence: 99%
“…The PI3K/Akt/mTOR pathway plays an important role in the regulation of the cells’ cycle; it impacts the development and differentiation of cells [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ]. The PI3K/Akt/mTOR signaling pathway plays an important role in the processes of tumorigenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Microtubule-associated protein light chain 3 LC3 and p62 are critical proteins in autophagy. In particular, cytoplasmic soluble LC3 (LC3I) is hydrolyzed during the autophagic process to form the membrane-bound LC3 (LC3II), with the increase in LC3II/I thus being indicative of enhancement of autophagy [33,34]. P62 binds to ubiquitinated proteins and interacts with LC3, mediating ubiquitinated protein transport in the autophagic progress [35].…”
Section: Discussionmentioning
confidence: 99%
“…It is highly indicative that expression of the LC3B autophagosome marker was found to be higher in node-positive vs. node-negative primary breast tumors and associated with an increased nuclear grade and shortened survival, and that higher expression of the autophagy-promoting factor Beclin-1 in triple-negative breast cancers (TNBCs) was correlated with an increase of lymph node and distant metastases in patients [7,8]. On the other hand, a number of autophagy-restraining isolated compounds and secretomes, including the histone deacetylase inhibitors and conditioned media which were examined in [9][10][11][12], have been shown to restore the inhibition of survival, the impairment of cell cycle progression, and the induction of cell death programs in breast cancer cell cultures [13][14][15]. Thus, with the warning to take the specific breast cancer subtype and treatment used into consideration, nevertheless, the cumulative preclinical data obtained prompt the development of novel autophagy-targeting agents as a valuable strategy to improve the efficacy of anticancer interventions.…”
Section: A Brief Insight Into Autophagy and Breast Cancer Cellsmentioning
confidence: 99%
“…This organism proved to be a good source of araguspongine/xestospongine alkaloids, dimeric 2,9-disubstituted 1-oxaquinolizidines that have been shown to possess a variety of pharmacological activities [51,52]. In 2015, Akl et al [53] reported that araguspongine C ((1R,8R,10S,15R,22R,29S)-9,30-dioxa-11,25-diazapentacyclo[20.6.2.2 8,11 .0 10,15 .0 25,29 ]dotriacontane-1,15-diol; Figure 8) exerted an antiproliferative effect on a panel of breast cancer cell lines in culture. More detailed analyses aimed at identifying the cause of the accumulation of vacuoles in BT-474 breast tumor cells revealed the dose-dependent ability of araguspongine C to stimulate autophagy, as revealed by the increase in the accumulation of fluorescent autophagosomes and the upregulation of the total protein levels of LC3, Beclin-1, and ATG-5, -7, and -16L1.…”
Section: Autophagy Modulators From Poriferamentioning
confidence: 99%